Partido dos Trabalhadores (PT): do núcleo inicial a sua consolidação na política do estado de Sergipe (1976-1987) - Nunes, Ronaldo de Jesus (2025)
The present study is dedicated to analyzing the emergence of the first nucleus of the Workers' Party in Sergipe (PT/SE) until its consolidation as a strong party in the field of state politics (1976-1987). The dictatorship was an authoritarian regime established in 1964, through a civil-military coup, which lasted until the 1980s, undergoing a "slow, gradual and safe" transition. The repressive actions represented a series of violations of citizens' rights, leaving marks and traumas in opposition social groups due to arrests, torture and murders. The Workers' Party (PT) of Sergipe was founded on July 28, 1980, led by trade unionists, students, teachers, workers and former members of the Brazilian Communist Party (PCB). Regarding the methodology, this research used the resources of oral history to produce some interviews with the founding members of the party, as well as with journalists who worked during the formation of the initial nucleus of the PT. In addition to these main sources, the research was carried out in Sergipe and Bahian newspapers, police and SNI reports and other documents collected by the State Truth Commission. The analysis and discussion of oral and written sources made it possible to study different historical times, but they are intertwined. Finally, the research aims to contribute to Brazilian historiography and especially Sergipe, in view of the interest in understanding the trajectories of characters in local history, who acted outside the major centers of the country, such as São Paulo, Rio de Janeiro and Brasília.